2017
DOI: 10.1098/rsos.160810
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in rotifer life history in response to stable isotope enrichment: testing theories of isotope effects on organismal growth

Abstract: In ecology, stable isotope labelling is commonly used for tracing material transfer in trophic interactions, nutrient budgets and biogeochemical processes. The main assumption in this approach is that the enrichment with a heavy isotope has no effect on the organism growth and metabolism. This assumption is, however, challenged by theoretical considerations and experimental studies on kinetic isotope effects in vivo. Here, I demonstrate profound changes in life histories of the rotifer Brachionus plicatilis fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…It is considered that the enrichment of a heavy isotope attenuates the biochemical reaction rate and delays the growth of an organism due to the kinetic isotope effect (2,(32)(33)(34). This view was supported by the findings of the present study using 13 C-enriched testosterone at physiological concentrations; 13 C-enriched testosterone on the alkaline phosphatase level of human osteoblasts.…”
Section: Discussionsupporting
confidence: 84%
“…It is considered that the enrichment of a heavy isotope attenuates the biochemical reaction rate and delays the growth of an organism due to the kinetic isotope effect (2,(32)(33)(34). This view was supported by the findings of the present study using 13 C-enriched testosterone at physiological concentrations; 13 C-enriched testosterone on the alkaline phosphatase level of human osteoblasts.…”
Section: Discussionsupporting
confidence: 84%
“…We found an overall trend of decline, which occurred when yeast cells get old, and elevating the HIC for hydrogen through heavy water feeding extended yeast lifespan by 84%. Our observation echoed the results of a previous study, which demonstrated that transient heavy water treatment extended lifespan in fruit flies, and more recently, another study showing that 15 N-enriched food extended lifespan in rotifers (Gorokhova, 2017;Hammel et al, 2013). These studies suggest that HIC elevation may produce a universal prolongevity effect, but before we could address this directly in mammalian animals, it is still unclear whether an overall HIC decline exists in mammals and for practical reason, whether HIC manipulation would promote longevity in model animals that are closer to human in biology.…”
Section: Introductionsupporting
confidence: 91%
“…It has been generally believed that enrichment of heavy isotope slow down the biochemical reaction rate and retard the growth of organism because of kinetic isotope effect [24][25][26][27][28]. This common view was supported by only a part of our findings.…”
Section: Discussioncontrasting
confidence: 47%